Rooting Response of Red Cedar (Toona ciliata M. Roem) to Some Physical and Chemical Treatments - Shamet, G.S.; Sharma, V.K. (Indian Journal of Agroforestry, 2020)
Cuttings of red cedar were tested for their rooting response under nursery condition to assess the effect of donor stage, preconditioning (girdling) and auxin/ chemical treatments during spring (Feb - March) and rainy (June-July) seasons. The girdled cuttings of seedling origin material exhibited significantly higher sprouting and rooting performance. A maximum 97.78% rooting was recorded when girdled cuttings from young donors were treated with 1% IBA+5% captan+5% sucrose-talc during spring season.